Effect of heat treatment on microstructure and mechanical properties of 34CrNiMo6 steel by laser solid forming. (June 2022) - Shi, Shang; Huang, Chunping; Liu, Fenggang; Chen, Wenjing; Liu, Fencheng; Xia, Chun
Abstract: 34CrNiMo6 steel was fabricated by laser solid forming technology. The effect of quenching and tempering treatment on the microstructure and mechanical properties was studied. The results showed that the microstructure of as-deposited samples consisted of martensite and bainite and tempered martensite. After quenching and tempering, the microstructure of the deposited layer was finer and became uniform, which was mainly tempered sorbite. When the sample was quenched at 830 °C and tempered at 460 °C, the microstructure was the tempered martensite. With the increase of tempering temperature, the content of carbide precipitated in martensite gradually increased. With the increase of quenching temperature, hardness of the samples increased firstly and then decreased. The hardness of the deposited layer gradually decreased with increasing the tempering temperature. The best quenching and tempering process for the laser solid forming 34CrNiMo6 steel was 830 °C quenching +540 °C tempering, which differed from the tempering treatment process for forged parts. The tensile strength increased from 980 MPa under the standard quenching and tempering conditions to 1230 MPa (increased by 25.5%) and the yield strength increased from 916 MPa under the standard quenching and tempering conditions to 1123 MPa (increased by 22.6%). But the elongation and percentage reduction of area obtained by the two quenching and tempering conditions were basically the same. The mechanical properties of LSFed 34CrNiMo6 steel after the optimal tempering treatment process had reaches the forging standard. The fracture mode of heat-treated LSFed sample was ductile fracture.